Weekly Variations of Short-Duration Maximal Jumping Performance in Soccer Players: Exploring Relationships With Accumulated Training Load and Match Demands - Silva, Rui; Clemente, Filipe Manuel; González-Fernández, Francisco Tomás; Bernardo, André; Ardigò, Luca Paolo (Frontiers in Physiology, 2021)
Purpose: The aim of this study was two-fold: (i) to analyze variations of short-duration maximal jumping performance in players exposed to a match and those who were not and (ii) to analyze the relationships between changes in the short-duration maximal jumping performance and different accumulated training load and match demands measures. Methods: Twenty-four professional soccer players (age: 20.3±1.7 years) were monitored daily for their training load and match demands over six weeks. Additionally, they weekly performed a short-duration maximal jumping performance test (72 h after the last match). Results: Negative moderate correlations were found between percentage of change of countermovement jump (CMJ) height and acute training load (ATL) of total distance (TD), high metabolic load (HML), accelerations (ACC) and decelerations (DEC) (r = -0.38, p= 0.004; r = -0.33, p= 0.013; r = -0.39, p= 0.003; and r = -0.30, p= 0.026). No correlations were found for match load (ML). TD, HML, ACC, and DCC were used to predict the percentage of change of CMJ height (r=.27, r=.25, r=.31, and r=.22). Conclusions: Match participation has negative effects on CMJ performance. The ATL of HML, ACC, DCC, and TD have a significant influence on both CMJ measures changes. Also, the ATL values of those metrics are the best predictors of the percentage changes of CMJ performance.